1985
DOI: 10.1002/j.1460-2075.1985.tb03730.x
|View full text |Cite
|
Sign up to set email alerts
|

A developmentally regulated cysteine proteinase in Dictyostelium discoideum.

Abstract: We have determined the sequence of a Dictyostelium mRNA encoding a protein with a high degree of homology to plant and animal cysteine proteinases. The degree of homology is highest in the region of the cysteine residue which is transiently acylated during peptide hydrolysis but all other residues known to be important in catalysis are also conserved. We have named this protein cysteine proteinase 1. There is a hydrophobic signal peptide of 18 amino acids and an additional 99 amino acids at the N terminus, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…Although all of these genes have been shown to be transcriptionally induced by cAMP and show similar developmental kinetics of expression, the only apparent similarity between the putative regulatory elements is that they are G/C rich (Williams et al 1980;Mehdy et al 1983;Mehdy and Firtel 1985;Pears et al 1985;Williams et al 1985;Datta et al 1986;Driscoll and Williams 1987;Pavlovic et al 1989). The rest of the 5'-flanking regions are >90% A/T, similar to the majority of the 5'-flanking regions of other Dictyostelium genes (Kimmel and Firtel 1983).…”
Section: Structure Of the G/c-rich Elementsmentioning
confidence: 94%
“…Although all of these genes have been shown to be transcriptionally induced by cAMP and show similar developmental kinetics of expression, the only apparent similarity between the putative regulatory elements is that they are G/C rich (Williams et al 1980;Mehdy et al 1983;Mehdy and Firtel 1985;Pears et al 1985;Williams et al 1985;Datta et al 1986;Driscoll and Williams 1987;Pavlovic et al 1989). The rest of the 5'-flanking regions are >90% A/T, similar to the majority of the 5'-flanking regions of other Dictyostelium genes (Kimmel and Firtel 1983).…”
Section: Structure Of the G/c-rich Elementsmentioning
confidence: 94%
“…The net cysteine proteinase activity is greatest during the vegetative phase, but declines during development as aggregation and then fruiting body formation take place. Cysteine proteinase genes which are not expressed during growth are switched on during this period (Pears et al, 1985;Williams et al, 1985); however, the products of these genes have not yet been identified. Spores have very low cysteine proteinase activity, but activity accumulates during germination (Jackson & Cotter, 1984;North & Cotter, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The gene is developmentally regulated, transcription commencing at the 6th hour of development and ceasing after 12 h of differentiation (Pavlovic et al submitted). Messenger RNA accumulation reaches a maximum between 8 and 12 h when it constitutes about 1% of the mRNA population (32,33). The messenger RNA can be accumulated prematurely when exogenous cAMP is present (34).…”
Section: Introductionmentioning
confidence: 99%
“…The messenger RNA can be accumulated prematurely when exogenous cAMP is present (34). It is approximately 1200 nucleotides in length and encodes a 36,000 dalton polypeptide (cysteine proteinase I) with a high degree of homology to plant and animal cysteine proteinases (33). Using the indirect end-labeling technique (2,35) we have mapped the micrococcal nuclease, DNase I and endogenous hypersensitive sites at the 5' and 3' flanking regions of the gene.…”
Section: Introductionmentioning
confidence: 99%